(untitled) (Journal of actual problems of jurisprudence, 2015)
According to the study of scientific work in the article examines the legal basis of regulation of a bank secrecy. Based on the opinion of the Kazakh and Russian scientists have made findings and made suggestions. Focuses on the shortcomings of disclosure of this concept in the legislation of the Republic of Kazakhstan.